Improving Pakchoy (Brassica rapa L.) Growth and Yield in Stone Waste–Contaminated Soil Through Organic Amendments - Ida Setya Wahyu, Atmaja; Riyan , Bagaskara; Hudhan Nur , Fath; Arief Yudistira , Wibawa (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
Rock flour (slurry), a by-product of the stone industry, contributes to soil degradation by causing soil compaction and reducing soil fertility. The sustainable strategies such as the application of organic amendments are needed to restore soil properties. The aim of this research to evaluate the effects of different organic amendments—rice husk biochar, straw compost, and goat manure—on the growth and yield of pakchoy (Brassica rapa L.) cultivated in stone waste–contaminated soil. This research used randomized block design with four treatments and five replications was employed: (P1) control (stone waste–contaminated soil without amendment), (P2) Stone waste–contaminated soil and husk biochar (1:1), (P3): Stone waste–contaminated soil and straw compost (1:1), and (P4): Stone waste–contaminated soil and goat manure (1;1). The results showed that goat manure significantly enhanced pakchoy growth parameters, including plant height, number of leaves, root volume, and plant weight. Goat manure promote the optimal plant growth through serve optimal planting media.